Implementing Syntax Evolution of Embedded Systems - Sasi Bhanu Jammalamadaka; Vinaya Babu A; Trimurthy P (Institute of Advanced Engineering and Science, 2015)
Safety critical systems such as nuclear recator systems cannot be shutdown as restrating is a huge process and incurs heavy cost. The embedded systems which are used for monitoring and controlling the safety critival systems cannot be shut down as well. ES systems which drives safety critical systems must be communicated from remote locations generally through a HOST connected on to Internet. Communication between the HOST and ES system is done using commnd lanaguage which has to be evolved from time to time. The chnage to the commnd lanauage must be undertaken while the embedded system is up and running, the evolution thus must be dynamic. Many architetcuers have been propsoed in the lieteratuer for evolving synatx of command lanaguage.The implemntaion of effcient architetcuer as such has not been found in the literatuer without which existing architetcuer as such has no menaing.The paper presntes a set of methods using which the syntax evolution of embedded systems as such can be achived. The synatx evolution methods have been applied to a safety critical system that monitors and controls tempartuers within a Nuclear recator system.